Perintah Menggunakan Sinyal Suara dengan Mel-Frequency Cepstral Coefficients (MFCC) dan K-Nearest Neighbor (KNN) - Aryo Widano, Gusti Putu; Karyawati, Anak Agung Istri Ngurah Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Technological developments today allow every action that originally required more energy to complete will become more practical, an input to give a command can not only be done with a mouse, keyboard, or touch screen technology but can also be done with the help of voice with the help of data by the user computer. Before it can be used as a command, first go through the voice feature extraction process using the Mel-Frequency Cepstral Coefficients (MFCC) method and the classification process using the K-Nearest Neighbor (KNN) method. Previously someone conducted a similar study, with the classification used being Learning Vector Quantization (LVQ) and the highest accuracy obtained ? 0.1.